PERAN STUDENT CARE DALAM MENINGKATKAN KESEHATAN MENTAL DAN KEMAMPUAN AKTUALISASI DIRI PADA MAHASISWA (STUDI KUALITATIF DESKRIPTIF DI UNIVERSITAS KATOLIK SOEGIJAPRANATA) - Kurniasih, Indit; Fransiska Tyas Meirani; Rini Sugiarti; Fendy Suhariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the role of student care in improving the mental health and self-actualization abilities of Unika Soegijapranata students. The research method used in this research is a descriptive qualitative method, and data collection is carried out through interviews and literature study. Interviews were conducted with the management of Unika Student Care (USC), Soegijapranata Student Career Center (SSCC), students, and alumni of Unika Soegijapranata. From the research results, it was found that Student Care has a positive role in improving the mental health and self-actualization abilities of Unika Soegijapranata students, where students can finally overcome the problems they face and are able to go through lectures well, be more confident, and be able to graduate on time and be able to determine their future career.